Silver ion exchange fillers incoporated with mixed matrix membrane for antibacterial application - Moslehyani, Ali (2012)
The objective of this work is to investigate silver ion exchanged fillers in the mixed matrix membrane for antibacterial application. Flat sheet Polyethersulfone (PES) mixed matrix membrane (MMM) was fabricated and characterized. MMM was fabricated using a dry/wet phase inversion technique. The work was performed to investigate the effect of incorporating Ag+-ion exchanged halloysite nano tubes (HNT) clay as large pore size filler in MMMs for bacterial removal. The chemical modification of HNTs involved silylation and Ag+-ion exchanged treatment. The silylated HNTs was prepared by treating them with N- )) (aminoethyl)- - aminopropyltrimethoxy silane agent. It is interlude to show that Ag+-ion exchanged fillers can control the Ag+ leaching to very low amount which was 14 ppb during fabrication and 11 ppb during filtration. Membrane characterization were performed using Fourier Transforms Infrared (FTIR), Field Emission Scanning Electron Microscopy (FESEM), energy dispersive X-rays (EDX), atomic absorption spectroscopy (AAS). The differential coliform agar (DCA) was used as antibacterial test. Escherichia coli (E-coli) were considered as a typical bacteria in this study. A fabricated PES asymmetric MMM flat sheet membrane successfully removed bacteria from the treated water, whereby, almost all bacteria have been inhibited.